Comment: Issue of Foreign Exchange Management in U.S. Multinationals - Kwan, Cheukuen (Journal of Financial and Quantitative Analysis, 1974)
Rita Rodriguez's paper examines the factors involved in the decisions of foreign exchange management. It consists of four major parts: a) the concept and definition of foreign exchange risk, b) the finance function and foreign exchange management, c) management's attitudes towards foreign exchange risk, and d) the effect of differences in management's attitudes towards foreign exchange risk on the monetary system. The conclusions and results of the paper are drawn from surveys and interviews with over 50 multinational corporations in the United States.